Mucosa-associated lymphoid tissue lymphoma of the right colon: a rare presentation - Sousa, Inês A.; Rama, Nuno J.; Sales, Inês F.; Ferreira, Marisa C.; Cunha, Maria F. (International Surgery Journal, 2025)
Mucosa-associated lymphoid tissue lymphoma (MALT) lymphoma affects frequently the gastrointestinal tract, most commonly the stomach. The colon is rarely affected. Both clinical presentation and endoscopic findings are variable and the histopathological with immunohistochemical analysis are needed for diagnosis. There are several treatment modalities available, with low remission rates and favorable outcomes. We present the case of an 80-year-old man who, after a positive screening faecal occult blood test, underwent a total colonoscopy which revealed an ulcerated lesion in the hepatic flexure of the colon compatible with lymphoma. After a staging CT scan of the chest, abdomen and pelvis without relevant findings except for a narrowing of the lumen of the hepatic flexure of the colon (where the tumor was located), the case was discussed by a multidisciplinary team, and it was decided to operate the patient. He underwent a laparoscopic right colectomy which was uneventful. Histopathological analysis of the surgical specimen, combined with immunohistochemistry, showed colonic MALT lymphoma. The patient subsequently completed staging with bone marrow aspiration (negative for lymphoma involvement) and respiratory testing for Helicobacter pylori, which was also negative. The patient has been followed for four years without recurrence and is completely asymptomatic. Colonic MALT lymphoma is rare and lacks characteristic presentation and diagnostic features. Surgical resection is a good therapeutic option.